La Argentina de los '90: Representaciones de identidades juveniles en la narrativa contemporánea - Giovannini, Silvina (Centro de Investigaciones de la Facultad de Filosofía y Humanidades, 2012)
Within the framework of the deep processes of transformation experienced during the Menemism period (deinstitucionalization, social exclusion, depoliticisation, blurring and fragmentation of the social imaginary), we consider that young people are the ones who exhibit more clearly these new conditions of existence. As subjects of specific practices and holders of an specific knowledge, the youth define their identity features in a changeable, dynamic and conflictive way. We are interested in inquiring the types of youth representation and focus specifically on the narrative of the complex link between young people and politics. From a discursive perspective, we tackle a series of short fictions which belong to Juan Forn, Martín Rejtman and Guillermo Saccomano: these writers circumscribe in the Argentinian context of the nineties and present young characters of social referential statute. We worked with the category "manchas temáticas" (thematic spots) by David Viñas (from Drucaroff, 2011) to identify the recurring topics in the developed corpus: the apathy, the errancy, the retreat into the innermost and see how these operate in the representation of the youth literary subjectivity that we analyze.